Dermoscopy, Line-Field Confocal Optical Coherence Tomography, Reflectance Confocal Microscopy, and Ultra-High-Frequency Ultrasound: Clues for the Diagnosis of Hidrocystomas - Erasti, Maria; D’Onghia, Martina; Batsikosta, Anastasia; Suppa, Mariano; Tognetti, Linda; Cappilli, Simone; Peris, Ketty; La Marca, Francesca; Perrot, Jean Luc; Rubegni, Giovanni; Rubegni, Pietro; Cinotti, Elisa (Diagnostics (Basel), 2024)
Background/Objectives: Hidrocystomas, eccrine and apocrine, are rare cystic lesions that form benign tumors of the sweat glands. This study aimed to describe the clinical features of hidrocystomas and evaluate the role of non-invasive imaging techniques, including dermoscopy, Line-field Confocal Optical Coherence Tomography (LC-OCT), Reflectance Confocal Microscopy (RCM), and Ultra-High-Frequency Ultrasound (UHFUS), in their diagnosis. Methods: In total, seven cases of hidrocystomas were collected from the Dermatologic Clinic of the University of Siena, Italy. Predefined dermoscopic, LC-OCT, RCM, and UHFUS features were retrospectively described. Results: Overall, hidrocystomas were located on the face, mainly presenting as blue/purple-bluish translucent papules (71%). Dermoscopic examination revealed a homogeneous purple-bluish color (71%), white pale halo (71%), and shiny globules at the periphery (57%). LC-OCT identified a hyporeflective cupoliform round structure in the dermis with a bright and thick contour, while UHFUS showed a round structure in the dermis filled with hypoechoic content. Conclusions: Non-invasive imaging techniques could significantly enhance the diagnostic accuracy of hidrocystomas, aid in differentiation from other lesions, and minimize unnecessary biopsies.